Psychological and sexual distress in rectal cancer patients and partners. Issue 6 (20th January 2022) - Acquati, Chiara; Hendren, Samantha; Wittmann, Daniela; Reese, Jennifer Barsky; Karam, Eli; Duby, Ashley; Dunn, Kelli Bullard; Kayser, Karen
Abstract: Background: Rectal cancer (RC) patients experience unique sources of distress, including sexual dysfunction and body image concerns, which can also cause distress among partners. This preliminary study investigated patterns of psychological distress, sexual functioning, sexual distress, and relationship satisfaction among RC patient‐partner couples at pivotal points during cancer treatment. Methods: Twenty couples participated ( N = 40). Patients and partners completed a series of validated measures of psychological distress (ET), sexual functioning (FSFI; IIEF), sexual distress (GMSEX; Sexual Distress Scale) and relationship satisfaction (GMREL) at time of diagnosis, 3 weeks after radiation, 4 weeks post‐surgery, and after chemotherapy and surgery for ostomy closure. Descriptive statistics, t ‐tests, and repeated‐measures ANOVA were used to analyze scores over time, first for patients and partners, and then by sex. Results: Relationship satisfaction remained elevated over time. In this sample, 55% of patients and 78.9% of partners reported clinically significant rates of psychological distress at diagnosis, which decreased to 23% and 46% respectively at the last assessment. Sexual satisfaction and distress worsened for patients and partners between baseline and surgery for ostomy closure. Both male and female participants reported statistically significant declines in sexual function from baseline to end of treatment ( p < 0.05). Discussion: Relative to relationship satisfaction, psychological and sexual health outcomes seem more vulnerable to the effects of RC treatment during the first year after diagnosis, both for patients and partners and for men and women. Results support the need for psychosocial care and sexual education/counseling for couples coping with RC.